Decision-support tools for diagnosing and selecting the optimal method of repairing buildings - Walczak, Zbigniew; Ksit, Barbara; Szymczak-Graczyk, Anna (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
This study introduces an innovative algorithm that leverages terrestrial laser scanning (TLS) and the fuzzy analytic hierarchy process (FAHP) for the optimization of building repair methodologies. Focusing on multi-criteria decision-making (MCDM), itshowcases a methodology for evaluating and selecting the most effective repair strategy for building elements, balancing various conflicting criteria. The research applies TLS for rapid and accurate geometric data acquisition of engineering structures, demonstrating its utility in structural diagnostics and technical condition assessment. A case study on a single-family residential building, experiencing floor deformation in a principal ground-floor room, illustrates the practical application. Maximum deflection and floor deflection distribution were measured using TLS. Utilizing FAHP for analysis, the decision model identifies the most advantageous repair method from a building user’s perspective. This approach not only provides a systematic framework for selecting optimal repair solutions but also highlights the potential of integrating advanced scanning technologies and decision-support methods in the field of building materials and structural engineering.